Revision of the guttata-group of Alona s. lato leads to its translocation to Prendalona Sousa, Elmoor-Loureiro & Santos, 2018 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y.; Sousa, Francisco Diogo Rocha; Elmoor-Loureiro, Lourdes M.a. (Zootaxa, 2023)
Revision of the guttata-group of Alona s. lato justifies its translocation to the genus Prendalona Sousa, Elmoor-Loureiro & Santos, 2018. Emended diagnosis of the genus and diagnoses for all its species are provided. Prendalona belong to the Hexalona-clade of Alona s. lato, it is a sister-group of genus Flavalona Sinev & Dumont, 2016, but differs from the latter in: (1) minute lateral head pores without any pockets below, (2) absence of the genital process on male postabdomen, and (3) absence of inner setae on endites 1–2 of thoracic limb I. Morphology of North American P. barbulata (Megard, 1967) and widely distributed P. guttata (Sars, 1862) is investigated in detail for the first time. Prendalona julietae sp. nov.,sibling-species of P. guttata, is described from Brazil. Global diversity and distribution patterns of Prendalona are discussed.